Novel CDK10 variants with multicystic dysplastic kidney, left ventricular non‐compaction, and a solitary median maxillary central incisor. Issue 3 (11th June 2021) - Darcha, Claude; Laffargue, Fanny; Boutaud, Lucile; Gallot, Denis; Dauphin, Claire; Garcier, Jean Marc; Achaiaa, Amale; Nitschke, Patrick; Fourrage, Cécile; Goumy, Carole; Attie‐Bitach, Tania
Abstract :